Manufacture of Concrete Paver Blocks with Recycled Demolition Waste - G. Balasubramanian; D. Salvia; D. Bharathi (Electronic Journal of Structural Engineering, 2020)
Due to rapid urbanization there is a great increase in building construction, so is the demoli-tion. There is no proper disposal of the demolition waste. About 530 million tons of C&D waste is generated annually. But only a few amounts of demolished concrete is recycled or reused. In this study, experimental investigations have been carried out to evaluate the effect of complete replacement of fine aggregate by dem-olition waste on compressive strength, which is compared with a conventional block. The concrete blocks were made in M20 mix. Further, the test was carried out in concrete paver block, in M40 mix design. The concrete paver blocks show 91% strength attainment at 28 days and it is only a marginal deterioration in the compressive strength. Therefore, the concrete blocks made with demolition waste can be used in low load bearing pavements.